2020
DOI: 10.1055/a-1205-0161
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic-Umbilical-to-Cerebral Ratio – A Novel Ratio Combining Doppler Parameters and Amniotic Fluid Volume to Predict Adverse Perinatal Outcome in SGA Fetuses At Term

Abstract: Purpose Introduction of a novel ratio – the amniotic-umbilical-to-cerebral ratio (AUCR) – to predict adverse perinatal outcome in SGA fetuses at term and comparison of its predictive accuracy with established parameters. Materials and Methods This retrospective cohort study included 165 singleton pregnancies with SGA fetuses (birth weight < 10th percentile) at term. Cases with planned vaginal delivery and documented pulsatility indices (PI) of the umbilical artery (UA), middle cerebral artery (MCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 32 publications
(41 reference statements)
2
7
0
Order By: Relevance
“…We found that, among the other single Doppler parameters, only the UA PI was a good predictor for APOs; MCA PI and UtA PI were not significantly different for APOs. This result is similar to the study by Stumphe et al 20 and we think that only UA PI is useful for predicting APOs in FGR pregnancies. The UtA Doppler measurement may be useful in pre‐eclamptic pregnancies, but it is not valuable for FGR fetuses.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…We found that, among the other single Doppler parameters, only the UA PI was a good predictor for APOs; MCA PI and UtA PI were not significantly different for APOs. This result is similar to the study by Stumphe et al 20 and we think that only UA PI is useful for predicting APOs in FGR pregnancies. The UtA Doppler measurement may be useful in pre‐eclamptic pregnancies, but it is not valuable for FGR fetuses.…”
Section: Discussionsupporting
confidence: 92%
“…Finally, the AUCR = SDP / UCR (UA PI/MCA PI) decreases in term FGR fetuses. Stumphe et al 20 first studied the AUCR and claimed that it was superior to single Doppler measurements, such as UA PI, MCA PI, and UtA PI, and was also superior to Doppler ratios, such as CPR and UCR. These results are similar to our findings.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations